RAW MATERIAL SUPPLY SYSTEM INFORMATION PT. COMFORT AIRE ANEKA TECHNIC - Yatono Yatono; Ir. Aqwam Rosadi K, MMSI (Jurnal Sistem Informasi, 2001)
Raw materials inventory system at PT.Comfort Aire Aneka Technic stillmenggunakansistem manually, which causes the system procedures haveshortcomings and weaknesses that have not been able to optimize vehicle is inproviding information quickly and accurately.The purpose of this paper is to design a computer-based information system thatfocuses on raw materials inventory information system located on the logistics of PT.Comfort Aire Aneka Technic . So that can be developed a system that could expeditethe process of service and information needs for management and stakeholders. Thissystem can also produce fast and accurate information in the form of reports and data